Transregional Airlift Networks - Larisa A. Ismagilova; Tatyana Matyagina; Larisa V. Sitnikova; Nikolay Smolyaninov (Communications of International Proceedings, 2020)
Airports being a component of the air transport infrastructure make a significant impact on the economy of regions; on the other hand, the airport business performance is largely dependent on the regions’ development. The article presents the results of analyzing a trans-regional market of airlift transportation, shows the connection and mutual dependence between the regional airport development strategies and the territory development strategies.
Keywords: airlift transportation market; transregional transport network; airport business; development strategy